Alcune riflessioni preliminari per una socio-logica del riso come fenomeno d’ordine - Spreafico, Andrea (SocietàMutamentoPolitica, 2020)
Laughter is an omnipresent social phenomenon in the life of individuals and, in its various forms, it accompanies their interacting, or even better, it contributes to its orderly realization. Although it is so common, it is polyvalent, ambiguous and difficult to grasp. Therefore, in the article we will try to take some steps in the direction of delineating a socio-logic of laughter, regarded both as a phenomenon of order and as a mode of social action.